Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Pertumbuhan Ekonomi terhadap Belanja Modal Pemerintah Daerah Kabupaten Magetan - Mutiara Intan Gamela; Arif Hartono; Ika Farida Ulfah (Universitas 45 Surabaya, 2024)
This research aims to determine the effect of local revenue, general allocation funds and economic growth on capital expenditure. The population in this study is the regional budget and expenditure realization report, and the Magetan Regency regional government's economic growth report for 2013 – 2022. The data used in this research is secondary data obtained from the Magetan Regency regional financial and asset management revenue agency. The independent variables in this research consist of local revenue, general allocation funds and economic growth, while the dependent variable is capital expenditure. The samples in this research are budget realization reports and economic growth reports with a period of 10 years. The sampling technique in this research used a non-probability sampling technique. This type of research uses a quantitative approach. Research data processing uses SPSS version 27 with multiple linear regression analysis methods. Based on the results of the analysis used, the results obtained are that local original income has no effect on capital expenditure, general allocation funds have an effect on capital expenditure, while economic growth has no effect on capital expenditure. Simultaneous testing shows that local revenue, general allocation funds and economic growth have no effect on capital expenditure.